2009
DOI: 10.1111/j.1551-2916.2009.02941.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ambient Gas and Temperature on Crystallization of Boron Nitride Spheres Prepared by Vapor Phase Pyrolysis of Ammonia Borane

Abstract: Synthesis of boron nitride spheres (BNS) was achieved by vapor phase pyrolysis of ammonia borane (BH 3 NH 3 ) using two independently temperature-controlled furnaces in a glove box filled with N 2 . The BNS were heated at 13001-17001C in flowing NH 3 , N 2 , or Ar by multistep heat treatment. The sizes of the BNS could be controlled by heating BH 3 NH 3 at different rates (11C/min: 300-800 nm, 51C/min: 300 nm-1.2 lm and 101C/ min: 300 nm-1.8 lm). The microstructures of BNS heated in different ambient gases wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 17 publications
1
15
0
2
Order By: Relevance
“…20,36). The reactions involved suggest that the nanoparticles are most likely a complex mixture of poly-aminoborane and its partially dehydrogenated derivatives, consistent with earlier reports 23,24,26,41 and our Auger investigations (Supplementary Fig. 3a-e).…”
Section: Resultssupporting
confidence: 92%
“…20,36). The reactions involved suggest that the nanoparticles are most likely a complex mixture of poly-aminoborane and its partially dehydrogenated derivatives, consistent with earlier reports 23,24,26,41 and our Auger investigations (Supplementary Fig. 3a-e).…”
Section: Resultssupporting
confidence: 92%
“…除了作为储氢材料, 氨硼烷还在以下几个方面 有广泛应用: (1) 还原剂, 把醛、酮羰基还原为醇 [48] , 在有异丙醇钛的情况下, 把醛和酮还原胺化为伯胺、 仲胺、叔胺, 产率为 84%~95% [135] , 还可以把 CO 2 还 原为甲醇 [136] 等; (2) 在材料领域用于制备 BN 材料, 如 BN 管 [137,138] 、BN 球 [139] 、制备白色石墨烯 [140] 等;…”
Section: 氨硼烷的其他应用unclassified
“…[9][10][11][12][13][14][15][16] Currently, there are only a few reports on the preparation of hollow BN spheres (HBNS). 6,[17][18][19] Since HBNS are usually produced from oxides or organic precursors, such as H 3 BO 3 and N,N-dimethylformamide, 17 the BN samples tend to contain O and C impurities. The use of a precursor without O and C as a starting material for preparation of BN is desired.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported the preparation of BN nanotubes, nanobamboos, nanofibers, and spheres with controlled sizes using an ammonia borane complex (BH 3 NH 3 ) as a starting material. 7,8,19 In a previous study, 19 it has been demonstrated that BN spheres composed of a crystallized shell and an amorphous core (core-shell BNS) are produced in NH 3 at high temperatures (>1300 C) by heating amorphous BN spheres (a-BNS) formed from BH 3 NH 3 . Hot H 2 O can dissolve a-BN but not crystallized BN.…”
Section: Introductionmentioning
confidence: 99%